The Welfare Effects of Bundling in Multichannel Television Markets - Crawford, Gregory S; Yurukoglu, Ali (American Economic Review, 2012)
We measure how the bundling of television channels affects short-run welfare. We estimate an industry model of viewership, demand, pricing, bundling, and input-market bargaining using data on ratings, purchases, prices, bundles, and input costs. We conduct simulations of à la carte policies that require distributors to offer individual channels for sale to consumers. We estimate that negotiated input costs rise by 103.0 percent under à la carte. These higher input costs offset consumer benefits from purchasing individual channels. Mean consumer and total surplus change by an estimated —5.4 to 0.2 percent and —1.7 to 6.0 percent, respectively. (JEL D12, L11, L51, L82, M31)